Evaluating Adherence to Medical Therapy in Patients with Chronic Heart Failure: Design and First Results of the COMPLIANCE Study - S. Yu. Martsevich; E. T. Guseynova; N. P. Kutishenko; Yu. V. Lukina; S. N. Tolpygina; V. P. Voronina; S. V. Blagodatskih (Рациональная фармакотерапия в кардиологии)
Aim. To study the adherence of doctors to the guidelines for the treatment of chronic heart failure (СHF) and the adherence of patients with СHF to the therapy prescribed by doctors.Material and methods. The COMPLIANCE study is an integral part of the PROFILE registry of the specialized cardiology division of the research center. The study includes patients with verified CHF who were previously observed in the PROFILE registry and patients with CHF who have been newly seeking medical care in the period from December 01, 2019 to December 31, 2020. At the first visit, the initial therapy was evaluated, treatment adherence was determined, and treatment was corrected in accordance with current guidelines. The second visit will also assess patient adherence to treatment, assess the factors of non-adherence and complications of diseases during the year of follow-up.Results. The first 30 case-records of patients with CHF included into the study were analyzed. 90% of patients received angiotensin-converting enzyme inhibitors (ACEI)/angiotensin receptor blockers (ARB). Beta-blockers (BB) were prescribed to 96.7% of patients, and mineralocorticoid receptor antagonists (MRAs) – to 76.7% of patients, and some of them received MRAs at ejection fraction >35%. It was found that the overall adherence of patients according to the adherence scale of the Russian National Society of Evidence-Based Pharmacotherapy (NSEPh) was significantly lower than the adherence to specific drugs. The worst was adherence to ACEI (71%) and MRAs (77%), higher – to BB (86%). The most common factors of non-adherence to treatment, according to the first results, are a large number of medications and a complex medication regimen.Conclusion. The first part of the COMPLIANCE study showed a relatively good adherence of doctors to current guidelines. However, the choice of the drug and its doses did not always correspond to evidence-based medicine data, existing guidelines and summary of product characteristics (SmPC) of specific drugs. The patients adherence to the prescribed therapy was not bad (this can be explained by long-term follow-up in specialized centers), but it was different for different drugs. The worst adherence was registered to the ACEI/ARB. This is warning factor, since these drugs make a significant contribution to improving the long-term outcome of CHF.